2017
DOI: 10.1149/2.0121801jes
|View full text |Cite
|
Sign up to set email alerts
|

Self-Discharge Effects in Lithium-Sulfur Equivalent Circuit Networks for State Estimation

Abstract: This study considers application-oriented models of lithium-sulfur (Li-S) cells. Existing ECN models often neglect self-discharge, but this can be important in applications. After describing the context in which control-oriented models and estimators are based, the self-discharge phenomenon is investigated for a new 21 Ah Li-S cell. As a contribution of this study, an equivalent-circuit-network (ECN) model was extended to account for cells' self-discharge. Formal system identification techniques were used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(41 reference statements)
0
5
0
1
Order By: Relevance
“…Moreover, Li-S batteries have 8-15% self-discharge rate per month (Kolosnitsyn and Karaseva, 2008) due to polysulfide shuttle (Mikhaylik and Akridge, 2004) and collector corrosion (Song et al, 2013), (Vaclav Knap et al, 2016), (Marinescu et al, 2015), which is between 10 and 15 times higher than the selfdischarge of Li-ion batteries (Table 1). Yousif et al conducted tests at different conditions on a 21 Ah Li-S cell, which showed that self-discharge is more significant as SOC increases (Yousif et al, 2018). Thus it is recommendable to store Li-s batteries at low SOC.…”
Section: Chemical and Physical Characteristicsmentioning
confidence: 99%
“…Moreover, Li-S batteries have 8-15% self-discharge rate per month (Kolosnitsyn and Karaseva, 2008) due to polysulfide shuttle (Mikhaylik and Akridge, 2004) and collector corrosion (Song et al, 2013), (Vaclav Knap et al, 2016), (Marinescu et al, 2015), which is between 10 and 15 times higher than the selfdischarge of Li-ion batteries (Table 1). Yousif et al conducted tests at different conditions on a 21 Ah Li-S cell, which showed that self-discharge is more significant as SOC increases (Yousif et al, 2018). Thus it is recommendable to store Li-s batteries at low SOC.…”
Section: Chemical and Physical Characteristicsmentioning
confidence: 99%
“…The SOC can reflect the remaining capacity of the battery, and the battery usage strategy can be planned through the known remaining capacity, so that the lithium‐ion battery can be operated in the best working condition and the longest service life by adjusting the voltage and current 3 . Therefore, real‐time and accurate estimation of the SOC will provide significant help to battery management 4–6 . However, due to the complex internal structure of the lithium‐ion battery itself, the SOC of the lithium‐ion battery is affected by various complex factors such as self‐discharge current, self‐discharge effect, internal temperature, external ambient temperature, and battery aging, which makes it difficult to accurately estimate out the value of SOC 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, real-time and accurate estimation of the SOC will provide significant help to battery management. [4][5][6] However, due to the complex internal structure of the lithium-ion battery itself, the SOC of the lithium-ion battery is affected by various complex factors such as self-discharge current, self-discharge effect, internal temperature, external ambient temperature, and battery aging, which makes it difficult to accurately estimate out the value of SOC. 7,8 In order to accurately estimate the SOC of lithium-ion batteries, relevant scholars have conducted a lot of research and proposed many methods for SOC estimation.…”
Section: Introductionmentioning
confidence: 99%
“…realizaron pruebas en diferentes condiciones en una celda de Li-S de 21 Ah, que mostraron que la autodescarga es más significativa a medida que aumenta la SOC (Yousif et al, 2018). Por lo tanto, es recomendable almacenar las baterías de Li-S a un nivel bajo de SOC.…”
Section: Capítulo 9: Difusión De Resultadosunclassified